Design, development and construction of a medical wrist rehabilitation device - Seabra, Eurico (2019)
The research and development of new kinds of technologies to support the recovery of human injuries have orientated the design, development and construction of new devices for the treatment and rehabilitation of wrist injuries. With limited founds, the construction of a new prototype was carried out with off-the-shelf components. After a detailed research and design work, the obtained device can be divided into two main components: it is capable to provide an adequaterehabilitation of the wrist and adequate proprioception exercises, allowing the patient to relax and to decrease the focus of pain.The development and construction of the device upholds the idea of portability, multifunctional operation and special designed hardware and software control, so it can be simple and user-friendly, allowing the control over the progress of rehabilitation with data recording for later analysis by physiotherapists and/or patients without any special training. The mentioned multifunctional operation, low-cost, user-friendly and portability makes it a good choice when compared to other complex robotic rehabilitation devices. This paper will present, discuss and analyse the proposed portable device, as well as its ability for the purpose of wrist rehabilitation.